2017
DOI: 10.1371/journal.pone.0186285
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and challenges of incorporating citizen science into university education

Abstract: A common feature of many citizen science projects is the collection of data by unpaid contributors with the expectation that the data will be used in research. Here we report a teaching strategy that combined citizen science with inquiry-based learning to offer first year university students an authentic research experience. A six-year partnership with the Australian phenology citizen science program ClimateWatch has enabled biology students from the University of Western Australia to contribute phenological d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 28 publications
1
73
0
3
Order By: Relevance
“…Notwithstanding the limitations in our study, we had similar results to many previous studies (Jordan et al 2011; Mitchell et al 2017; Silva et al 2016; Bonney et al 2016; Phillips et al 2018). They suggest that citizen science projects can be a valuable tool in the palette of environmental education.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Notwithstanding the limitations in our study, we had similar results to many previous studies (Jordan et al 2011; Mitchell et al 2017; Silva et al 2016; Bonney et al 2016; Phillips et al 2018). They suggest that citizen science projects can be a valuable tool in the palette of environmental education.…”
Section: Discussionsupporting
confidence: 89%
“…While students mainly participated in the collection of data, as our project was contributory, this still led to potential substantial learning, although it has been suggested that learning outcomes are improved if participants are able to participate in many different aspects of a project (Zoellick, Nelson, and Schauffler 2012). As in previous research, students reported factual knowledge on study species and their near environment (Jordan et al 2011; Mitchell et al 2017; Silva et al 2016) and procedural knowledge on used research protocols (Bonney, Cooper, et al 2009; Bonney et al 2016). In comparison, conceptual knowledge was not as well represented in students’ responses; for example, in a number of interviews students did not know what “urban ecosystem” meant.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In addition, new sources of data are being acquired all the time which means that the potential issues with resolving station locations may be an ongoing challenge. For example, we are working closely with the C3S Data Rescue Service to ensure that all rescued climate data is deposited via the new data discovery and depo-sition web-based service which we are developing (Noone et al, 2019). Work is also ongoing in collaboration with the European Environmental Agency (EEA) in its capacity as the Copernicus in situ lead, and with ECMWF in its capacity as the entrusted entity for C3S.…”
Section: Discussion and Future Plansmentioning
confidence: 99%
“…Benefits accrue to classrooms that use citizen science approaches to teach science (Kountoupes and Oberhauser, 2012;McDonald, 2014). These benefits include increased engagement in local environmental issues, awareness of the potential for faulty data, and becoming more careful in collecting data (Mitchell et al, 2017).…”
Section: News and Viewsmentioning
confidence: 99%